NEW APPROACH TO DETERMINING AXIAL CRITICAL LOADS SHELLS, PLATES AND RODS - Todchuk, Volodymyr (Proceedings of National Aviation University (archive), 2019)
Purpose: To show that one of the reasons for the large difference between the calculated and experimental critical loads is the incorrect interpretation of the buckling process. Methods: The energy criterion of stability and the relation of the general linear theory of thin-walled structures are used. Results: New formulas for critical loads of shells and plates have been obtained. Discussion: To estimate the bearing capacity of engineering structures, precise formulas are needed to calculate the critical loads under axial compression. Such formulas have not yet been obtained. The reason for the large discrepancies between the theoretical and experimental values of the axial critical loads of cylindrical shells was not found. In this paper, an attempt was made to solve this problem. In contrast to the usual approach, it is assumed here that when the structure is buckled, the distance between the loaded ends does not change. This allowed us to obtain new formulas for axial critical loads. The values of critical loads calculated by these formulas are close to the experimental data. Based on this, it was concluded that the formulas obtained can be used for real calculations of the critical loads of cylindrical shells and plates, and the proposed approach can be used to continue studies of the stability of thin-walled structures.